From pilots to practice: a governance-technology integration framework for circular water in the baltic sea region - Cordeiro, Cheryl Marie; Sindhøj, Erik (Frontiers in Earth Science, 2026)
The Baltic Sea Region (BSR) is a major arena for circular water innovation, supported by EU investment exceeding €20.5 million in recent years. Yet moving from technically successful pilots to wider regional implementation remains difficult. This study inquires into how governance–technology integration is framed and enacted across policy, practitioner discourse, and project implementation in circular water management, and what coordination processes appear to support scaling. We combine a three-tier, mixed-method analysis of a 372,856-token corpus. Tier 1 covers 12 EU/HELCOM/EUSBSR policy documents (supranational and macro-regional framing). Tier 2 analyses seven Europe Forum Turku transcripts (135,151 tokens; 2024–2025), comprising 526 coded practitioner and policymaker statements, using keyword/collocation analysis and semantic network metrics. Tier 3 compares five Interreg BSR projects representing diverse technology–governance configurations, drawing on project documentation and implementation records. Results show a temporal shift in practitioner discussions away from stand-alone technical optimisation language toward framing that more explicitly links technology to regulation, institutional responsibility, and strategic priorities such as resilience and security. Across policy, forum, and project levels, three coordination mechanisms recur as central to scaling: (i) structural coordination through cross-border policy platforms and regulatory alignment, (ii) knowledge coordination via practitioner forums that translate policy priorities into shared technical and operational repertoires, and (iii) temporal coordination that aligns policy cycles and funding horizons with technology development and deployment timelines. This data-driven study illustrates that scaling in circular water management depends on adaptive coordination across institutional scales, not only on technological performance. Making coordination requirements explicit can improve the effectiveness of public investment and strengthen pathways from pilots to regional practice. In doing so, it proposes a cross-scale coordination lens to locate where scaling stalls between policy intent, practitioner translation, and post-pilot implementation.